Effects of cover crops on phosphatase activity in a clay arable soil in the UK - Reynolds, S.H.; Ritz, Karl; Crotty, F.V.; Stoate, C.; West, H.; Neal, Andrew L. (Wiley, 2017)
The effect of five cover crop species (radish, buckwheat, vetch, phacelia and oat) alongside an un-cropped control, on the activity and persistence of soil acid and alkaline phosphatase activity was investigated. There was no effect on alkaline phosphatase activity at the time of cover crop incorporation (March), but by the point of maturation of the following oat cash crop (June) significant differences were detected, with the greatest activity following an oat cover crop. Acid phosphatase activity showed species-related significant differences at both sampling dates, with the magnitude increasing by June. Again, plots following an oat cover crop showed the greatest activity, followed by phacelia. This has shown that soil phosphatase enzymes are affected by the presence of a cover crop, that this effect is apparently species-dependent – and not dependent on the amount of biomass from the cover crop – and that cover crops could be a potential means to enhance soil phosphorus cycling.